Conemporary Danish Architecture- Humanity and Rationality - Csépke, Tamás; Szentirmai, Tamás (International Journal of Engineering and Management Sciences, 2017)
In my study I have examined the characteristics of contemporary Danish architecture and the way how they formed. In Denmark, there is strongly rooted social atmosphere. The architectural efforts strongly reflects the social problems every time, considering the environmental aspects. The regionalist methods appear in the architecture, because of this the different architectural styles appear specific way. Self-reflective and analytical way the Danish architects try to answer the contemporary issues, even more emphasize the human factor.